Sağlıklı Çocuklarda Femoral Anteversiyon Artışının Hipermobilite Sendromundan Bağımsız Olarak Yürüme Parametrelerine Etkileri - Karaca, Gülşah (My University, 2018)
Introduction Increased femoral anteversion (İFA) is a transverse plane problem that may lead to alterations on lower body kinematics during walking (1,2). IFA and hypermobility syndrome are commonly seen together in healthy individuals (3). Therefore, describing the pure effects of IFA related gait parameters is very difficult for children with hypermobility and IFA together. Methods Sixty-seven participants were divided into four groups; 1)Twenty-eight hypo-mobile IFA children (Thoracantheric-Promience-Test(TPAT):45±4.2°) whose Beighton-score were <4 (IFA<4) (Age: 10.3±3.7y.o,Beighton:2.6±1.1), 2) Twenty-eight hyper-mobile IFA children (TPAT:45.5±6.5°) with Beighton Score >6 (IFA>6) (Age:7.7±3.7y.o, Beighton:7.8±0.9), 3)Seven hypo-mobile TDC (Hip-internal-rotation:<50°, TPAT: 19.1 ±8.3°) with Beighton-score <4 (N<4)(Age:12.1±1.4y.o, Beighton: 1.1 ±1.6) and 4)Five hyper-mobile TDC (TPAT:28.0±5.0°) with Beighton-score >6 (N>6) (Age:9.0±1.2y.o, Beighton:6.8±0.8), The pelvic, hip, knee and ankle kinematics and temoporal-spatial parameters were analyzed by 3D Motion Analysis in self-selected speed with Davis protocol (4). All participants with IFA had hip-internal-rotation:>65°, and external hip rotation angle >20°. Mann Whitney U and paired t test were used for comparison (p<0.05). The same parameters in which significantly changed between IFA<4 and N<4 and comparison of IFA<6 and N>6 were considered as pure IFA related gait parameters. Results Pure IFA affects were found as increasing peak dorsiflexion angle in swing, hip internal rotation in stance and peak pelvic external rotation and pelvic rotation range (Table 1). The hyper mobility related gait parameters were increased knee flexion at initial contact and peak knee extension, decreased peak and mean hip rotation and time of toe-off in stance. Discussion This study, the first in the literature, distinguished the IFA related gait parameters from hyper-mobility affects. Whether the hyper-mobility involves the IFA or not, IFA augments hip internal rotation, pelvic external rotation and increase the peak dorsiflexion in swing. Even though velocities are similar in all groups, IFA also may cause to set earlier toe-off time. In TDCs, only temporal-spatial parameters were found as changed, which may due to limited participation in TDC groups. Hypermobility may be a compensatory factor that decreases the enhanced hip internal rotation during walking for neurologically intact children with increased femoral anteversion.